Non-normative corporalities and transgender identity in English as a Foreign Language student teachers - Diego Ubaque-Casallas; Harold Castañeda-Peña (Asociación Colombiana de Profesores de Ingles, 2020)
Little international research exists on EFL (English as a Foreign Language) student teachers regarding transgender identity and non-normative corporalities. Similarly, few studies in Colombia have investigated the concept of teacher identity of transgender EFL student teachers to understand this dimension of identity. This study explores the transgender/blind identity of an EFL student teacher. The study took on identity as multiple and fluid to understand how transgender identity serves a lens to shape the process of becoming a teacher. Findings suggest that transgender identity is made from either experiences that modify or re-construct the self.  The study revealed that the notion of gender is contested when the idea of transgender works as a personal mechanism to question the existing normativity of one's own body and the self. Identity is then presented as a series of choices and performances situated in time that are validated in the transgender and blind condition.